High‐Throughput Approaches in Carbohydrate‐Active Enzymology: Glycosidase and Glycosyl Transferase Inhibitors, Evolution, and Discovery. (17th July 2019) - Chao, Lemeng; Jongkees, Seino
Abstract: Carbohydrates are attached and removed in living systems through the action of carbohydrate‐active enzymes such as glycosyl transferases and glycoside hydrolases. The molecules resulting from these enzymes have many important roles in organisms, such as cellular communication, structural support, and energy metabolism. In general, each carbohydrate transformation requires a separate catalyst, and so these enzyme families are extremely diverse. To make this diversity manageable, high‐throughput approaches look at many enzymes at once. Similarly, high‐throughput approaches can be a powerful way of finding inhibitors that can be used to tune the reactivity of these enzymes, either in an industrial, a laboratory, or a medicinal setting. In this review, we provide an overview of how these enzymes and inhibitors can be sought using techniques such as high‐throughput natural product and combinatorial library screening, phage and mRNA display of (glyco)peptides, fluorescence‐activated cell sorting, and metagenomics. Abstract : Enzymentdeckung : Hochdurchsatz‐Ansätze sind ein leistungsfähiges Werkzeug für Innovationen in der Enzymologie. Insbesondere die kohlenhydrataktiven Enzyme mit ihrer hohen Diversität können von neuen Entwicklungen auf diesem Gebiet profitieren. Dieser Kurzaufsatz diskutiert innovative Ansätze zur Entdeckung neuer Inhibitionsformen, zur Feinabstimmung der Enzymreaktivität und zur Suche nach neuen Enzymen.